The Transformation of Learning at Special Schools on The Learning from Home Policy During the Covid 19-Pandemic - Iva Evry Robiyansah (IJEBD (International Journal of Entrepreneurship and Business Development), 2020)
The transformation of learning at special schools during the covid-19 pandemic is done at home through the implementation of online learning. The aim of online learning is to provide the best teaching for students with special needs based on their potential and characteristics. The interesting and unique characteristics of students affects the important of management in online learning. Indeed, providing education services remains a top priority which can be done with respect to some components namely: 1) Enhance self-motivation and commitment, 2) Create schedule and learning journal once a week with regards to the characteristics of the students, 3) Collaborate and coordinate with parents and teachers, 4) Evaluate by providing ratings and give rewards to students so that students feel enthusiast during learning at home during in this covid-19 pandemic. The whole component is carried out in an integrated and continuous holistic manner, so that the transformation in the learning process in special schools can be carried out in line with students’ characteristics.